Prevalence of trypanosomes associated with drug resistance in Shimba Hills, Kwale County, Kenya - Kulohoma, B.W.; Wamwenje, S.A.O.; Wangwe, I.I.; Masila, N.; Mirieri, C.K.; Wambua, Lillian (Springer, 2020)
Objective Animal African trypanosomiasis (AAT) is a life-threatening vector-borne disease, caused by trypanosome parasites, which are principally transmitted by tsetse flies. In Kenya, the prevalence of drug-resistant trypanosomes in endemic regions remains poorly understood. The objective of this study was to establish AAT point prevalence, drug susceptibility of associated trypanosomes, and measure infectivity by multiple AAT mammalian hosts to tsetse flies in Shimba hills, a resource-poor region with high bovine trypanosomiasis prevalence and morbidity rates at the coast of Kenya. We collected tsetse flies using traps (1 Ngu and 2 biconical), and then sorted them on sex and species. Trypanosomes present in tsetse flies were detected by first extracting all genomic DNA, and then performing PCR reactions with established primers of the internal transcribed spacer regions. Polymorphisms associated with trypanocide resistance in the TbAT1 gene were also detected by performing PCR reactions with established primers. Results Our findings suggest low trypanosome prevalence (3.7%), low trypanocide resistance, and low infectivity by multiple mammalian hosts to tsetse flies in Shimba hills. We conclude that enhanced surveillance is crucial for informing disease management practices that help prevent the spread of drug-resistant trypanosomiasis.